Building of the enabled web-based GIS participation system: a tool to enhance community participation in city development plan - Devaraju, Anusuriya; Herman, Nanna Suryana; Sahib @ Sahibuddin, Shahrin (2007)
This research has been conducted under the frame work of GIS interoperability infrastructure financed by the Malaysian Ministry of Science and Technology. In this paper, we discuss the development and analyze the potential application of the Geographical Information System (GIS) and Internet computing to enhance community participation in the decision making processes i.e. in Local Plan of Block 3, Melaka Tengah district as a model. The focus of this paper is on the designing and development of the enabled Web-based GIS Participation System called, GISPSS. It is considered to be similar to a Real Time Resources Discovery Server but it comprises four main complimentary components: the Map Viewer, the Objection Support, the Planning Process Documentation, and the Web Content Management. The functional features of these components are highlighted. The multi-tiered architecture forms the basis of the Enabled Web based GIS system has been adopted in this research.